2019
DOI: 10.1097/sla.0000000000003725
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypocalcemia After Thyroidectomy

Abstract: Objective:The aim of the study was to determine severe hypocalcemia rate following thyroidectomy and factors associated with its occurrence.Background:Hypocalcemia is the most common complication after thyroidectomy. Severe post-thyroidectomy hypocalcemia can be life-threatening; data on this specific complication are scarce.Methods:Patients who underwent thyroidectomy in the American College of Surgeons-National Surgical Quality Improvement Program thyroidectomy-targeted database (2016–2017) were abstracted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
1
37
1
1
Order By: Relevance
“…Postoperative complications included hoarseness, hypocalcemia, choking, chylous leakage, postoperative infection, and so on. While the definition of postoperative hypocalcemia varies widely in literature (16,17), the diagnostic criteria used in this study were: blood calcium level below 2.1 mmol/L 1 week after total thyroidectomy, or the presentation of the following symptoms: muscle pain, muscle weakness, arrhythmia for the first time after surgery, tingling and numbness in the face and limbs, and tendon hyperreflexia; symptoms lasting more than 6 months were considered permanent hypocalcemia. The diagnostic criteria for permanent postoperative hoarseness in this study were: no improvement for more than 6 months and the presence of recurrent laryngeal nerve palsy was supported by laryngoscopy.…”
Section: Surgery and Follow-upmentioning
confidence: 99%
“…Postoperative complications included hoarseness, hypocalcemia, choking, chylous leakage, postoperative infection, and so on. While the definition of postoperative hypocalcemia varies widely in literature (16,17), the diagnostic criteria used in this study were: blood calcium level below 2.1 mmol/L 1 week after total thyroidectomy, or the presentation of the following symptoms: muscle pain, muscle weakness, arrhythmia for the first time after surgery, tingling and numbness in the face and limbs, and tendon hyperreflexia; symptoms lasting more than 6 months were considered permanent hypocalcemia. The diagnostic criteria for permanent postoperative hoarseness in this study were: no improvement for more than 6 months and the presence of recurrent laryngeal nerve palsy was supported by laryngoscopy.…”
Section: Surgery and Follow-upmentioning
confidence: 99%
“…Studies conducted by Sawant et al [14] show that postoperative complications after thyroidectomy affected 14% of the surveyed, while the research carried out by Cipolla et al [15] reports the value of up to 43.8%. Kazaure et al showed that 5.8% of 7366 patients had thyroid hypocalcaemia after thyroidectomy, 83.2% required intravenous calcium therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…As for thyroid surgery, patients need life-long thyroxine replacement therapy and possibly have abnormal low circulating parathyroid hormone (PTH) levels after surgery, which can lead to disorders of the calcium-phosphate balance ( Jørgensen et al, 2021 ). A study including 7,366 thyroidectomy patients showed that patients with severe hypocalcemia had a higher rate of recurrent laryngeal nerve injury (13.4% vs. 6.6%), unplanned reoperation (4.4% vs. 1.3%), and longer hospitalization (30.4% vs. 6.2%) ( p < 0.01) ( Kazaure et al, 2021 ).…”
Section: Management Of Graves’ Hyperthyroidism and Negative Effectsmentioning
confidence: 99%